2017
DOI: 10.1021/acsenergylett.7b00063
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Proton-Coupled Electron Transfer: Different Avenues for Promoting Proton/Electron Movement with Solar Photons

Abstract: Excited-state proton-coupled electron transfer (ES-PCET) is a promising avenue for solar fuel production and small molecule activation. Although less is known about ES-PCET reactions than related transformations involving exclusively thermal processes, ES-PCET holds promise as a simple and efficient reaction scheme for the formation of solar fuels, and it may provide access to new reactivity not accessible from ground electronic states. This review classifies ES-PCET into six categories based on the identity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
92
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 94 publications
4
92
0
Order By: Relevance
“…There is growing interest in the use of solar energy to drive these proton-coupled electron transfer (PCET) reactions. [1][2][3][4] To accomplish this feat, molecular systems that effectively couple light energy to proton and electron transfer are needed. Two approaches that have been utilized to couple light to PCET include the ash-quench technique, where photoexcitation of a sensitizer is followed by rapid electrontransfer quenching by a redox mediator to yield an oxidized or reduced sensitizer.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing interest in the use of solar energy to drive these proton-coupled electron transfer (PCET) reactions. [1][2][3][4] To accomplish this feat, molecular systems that effectively couple light energy to proton and electron transfer are needed. Two approaches that have been utilized to couple light to PCET include the ash-quench technique, where photoexcitation of a sensitizer is followed by rapid electrontransfer quenching by a redox mediator to yield an oxidized or reduced sensitizer.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen atom transfer originated by radicals is one of the most fundamental processes for several areas of chemistry, from biological processes, to chemical synthesis, materials science, hydrocarbon combustion or atmospheric chemistry. [1][2][3][4][5][6][7][8][9][10][11][12] In the context of the chemistry of the troposphere, the oxidation processes involving abstraction of hydrogen atoms by radicals are among the most important reactions and many of these processes are well known. 7,13 Very recently, it has been shown that the triplet excited state of SO 2 can react with water producing hydroxyl radicals and is the most oxidizing species in the Earth's atmosphere, 14 and it has also been predicted that this reaction is enhanced by several orders of magnitude at the air-water (airclouds) interface.…”
Section: Introductionmentioning
confidence: 99%
“…Dempsey et al. have classified the reactants involved in PCET reactions into several categories, one of the category being the excited state proton/electron donors, and have reviewed the recent advances and key discoveries in this area with respect to solar fuel production and small molecule activation …”
Section: Introductionmentioning
confidence: 99%
“…[17][18] Dempsey et al have classified the reactants involved in PCET reactions into several categories, one of the category being the excited state proton/electron donors, and have reviewed the recent advances and key discoveries in this area with respect to solar fuel production and small molecule activation. [19] Ruthenium polypyridyl complexes are investigated since the last decade due to their interesting photophysical and electrochemical properties and their potential applications. [4,[20][21][22][23][24][25][26][27] From a photochemistry point of view, there is a special interest in ruthenium (II) polypyridyl complexes especially those with long lived excited states.…”
Section: Introductionmentioning
confidence: 99%